Intensified Tpx3Cam, a fast data-driven optical camera with nanosecond timing resolution for single photon detection in quantum applications. (1st January 2023) - Nomerotski, A.; Chekhlov, M.; Dolzhenko, D.; Glazenborg, R.; Farella, B.; Keach, M.; Mahon, R.; Orlov, D.; Svihra, P.
Abstract: We describe a fast data-driven optical camera, Tpx3Cam, with nanosecond scale timing resolution and 80 Mpixel/sec throughput. After the addition of intensifier, the camera is single photon sensitive with quantum efficiency determined primarily by the intensifier photocathode. The single photon performance of the camera was characterized with results on the gain, timing resolution and afterpulsing reported here. The intensified camera was successfully used for measurements in a variety of applications including quantum applications. As an example of such application, which requires simultaneous detection of multiple photons, we describe registration of photon pairs from the spontaneous parametric down-conversion source in a spectrometer. We measured the photon wavelength and timing with respective precisions of 0.15 nm and 3 ns, and also demonstrated that the two photons are anti-correlated in energy.